Trabalho docente, políticas de avaliação em larga escala e accountability no Brasil e em Portugal - Richter, Leonice Matilde (2015)
The thesis aims to deepen studies on the new settings of assessment on a large scale and its impact on teaching work and the organization of school work, considering as an empirical field the Brazilian and Lusitanian realities. In relation to methodological aspects, we materialized the study through questionnaires and interviews in nine schools in Braga, Portugal, involving 35 subjects of the public network who work in Basic Education. In Brazil, the research embraced 29 schools, with the participation of 225 subjects, in which 141 work as teachers on 5th and 9th grades of elementary school, 55 Basic Education Specialists and 29 directors. We used as categories of analysis about the conditions of teaching work: the working conditions at school; the teacher s working conditions as a professional category; and working conditions for teacher s autonomy and authority in teaching. From the immersion in the empirical field, we evidenced objective and subjective effects of standardized tests on teaching, such as: cooperate to expand the school s commitment concerning the students education; the large scale assessment mostly contributes to the minimization of school autonomy, by imposing standard measurements; produce new compositions and formats for the school curriculum, as they direct evaluated subjects and contents; the evaluation is prioritized as the most powerful meritocratic and competitive process, in keeping with the market logic; the projection of the rate expansion in the assessments was not accompanied by significant improvements of the necessary conditions for the teacher s work in the educational process; assessment policies, to a certain extent, withdraw the responsibility of the State for the consolidation of structural changes for the quality of education and impute the teacher a unilateral responsibility for secure this improvement; in the managerial State model, the pattern of large-scale assessment is based on students performance on standardized tests; tests instigate the formation of new teachers values, subjectivities and teacher relationships with students, between coworkers and with the teaching practice, which follows an international tendency; there is a limited appropriation and use of indicators by school professionals as well as the State towards the consolidation of necessary public policies to guarantee the quality of education; and tests have engendered new demands of work, and to meet the external targets in precarious conditions of teaching work, the intensification of teachers work is strengthened.